Green solution to riparian pollution: Populus alba L. potential for phytoremediation and bioindication of PTEs along the Sava river - Zorana Miletić; Milica Jonjev; Snežana Jarić; Olga Kostić; Dimitrije Sekulić; Miroslava Mitrović; Pavle Pavlović (Heliyon, 2024)
This study addresses the potential of Populus alba L. for bioindication and phytoremediation of the contaminated lower part of the Sava River. The main objectives are to assess soil contamination with potentially toxic elements (PTEs: As, B, Cd, Cr, Cu, Li, Ni, Pb, Sr, and Zn), evaluate their availability, and assess the phytoremediation and bioindication potential of Populus alba. Quantification of the PTE contents was performed using inductively coupled plasma optical emission spectroscopy (ICP-OES), while bioindication and phytoremediation potential were evaluated using accumulation indices. The study revealed phytotoxic contents of Cr, Cu, Ni and Zn in the riparian soils of the lower Sava River. The percentage of available Cd was high, but due to its low total content, its phytotoxic potential is limited. According the metal accumulation index, Populus alba exhibits significant potential to accumulate the PTEs studied (with accumulated toxic contents of B, Cr, Li, Sr, and Zn). The ability of Populus alba to accumulate and bioindicate Cd, Cr, and Ni is promising, as is its ability to potentially remediate B, Cd, and Zn. Copper deficiency in leaves resulted in a reduction in photosynthetic performance, but without visible morphological symptoms. The reduced photosynthetic capacity serves as an adaptive strategy for this species in response to toxic levels of PTEs. Since Populus alba is widely distributed in European riparian forests, it is a good candidate to address soil contamination through phytoremediation and bioindication techniques.